(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
The article presents a semantic analysis of terminological metaphors in Spanish economic language. The aim is to identify and define the source domains in terminological metaphors describing abstract concepts in economics. It complements existing conceptual taxonomies in this field and shows that metaphorical terms are images of human existence and everything related to it. It also aims to determine which conceptual domain is the most frequent in the formation of metaphorical terms in economic language. It is shown that mind mapping reflects multiple spheres of life, human activities and everything around us. The results show that the largest number of source domains identified are from the environment of sciences such as physics or biology.